Pembiasaan Salat Duha Berjamaah sebagai Pembentukan Karakter Disiplin Siswa SDN 2 Sukorejo Ponorogo - Hidayatulloh, Ma'ruf; Setyowati, Nanik; Sholihah, Abdah Munfaridatus (Social Science Academic, 2024)
In Presidential Regulation Number 87 of 2017 concerning Strengthening Character Education, it is explained that this program is implemented by applying the eighteen values ​​of Pancasila in character education. These values ​​include religiosity, honesty, tolerance, discipline, hard work, creativity, independence, democracy, curiosity, national spirit, love of the country, respect for achievements, good communication, love of peace, interest in reading, concern for the environment. social awareness, and responsibility. Character Strengthening Education (PPK) is a government program that aims to form the nation's next generation who are academically intelligent and physically and spiritually strong. Strengthening character education can be done through habituation. One form of character training implemented by students at SDN 2 Sukorejo is the Duha prayer in congregation. This research aims to determine the benefits of holding Duha prayers at SDN 2 Sukorejo which were carried out during the Face-to-Face Pilot School Program within a period of two weeks in July 2024. The research method used was a descriptive qualitative method. The results of the research show that the habit of praying Duha in congregation as part of strengthening character education has a positive impact on student character, including increasing friendship between students, mutual respect and respect, the habit of remembering and getting closer to the Creator, reducing excessive individualism, and discipline comes. go to school on time, carry out positive activities repeatedly, and carry out religious teachings consistently. From these results it can be concluded that the habit of Duha prayer in congregation is very useful in cultivating positive character in students.